IDENTIFYING THE FIGURE OF THE QUEEN KALINYAMAT IN A HISTORICAL TEXT USING TRANSITIVITY SYSTEM - Nurhayati Nurhayati (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
The purpose of the study is to identify the characterization of the Queen Kalinyamat as one of the woman leaders in the Javanese kingdoms. Choosing the history text is interesting, because that is not fictional and imaginative text, but it was written by authors who have never seen and experienced the events they wrote. The bias and tendency of the authors are unavoidable. The study chose Peranan Ratu Kalinyamat di Jepara pada Abad XVI as the data source, and selected two chapters that talk about the Queen Kalinyamat. Data are clauses containing the noun group Ratu Kalinyamat and their derivate. To analyze the data, the researcher used transitivity system as the theoretical framework. The result shows that the authors describe two sides of the Queen character, those are the personal and the social characters. The characterization was realized through describing what the Queen did, thought, felt, and the Queen temper and physical appearance. The systemic functional linguistic approach offers other possibilities to construct the figure of the Queen Kalinyamat.